Pengaruh Kepemimpinan dan Supervisi Akademik Kepala Sekolah terhadap Kinerja Guru - Okta Wari Wijaya; Nur Ahyani; Mulyadi Mulyadi (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to determine and describe the influence of the principal's academic leadership and supervision, both simultaneously and partially, on teacher performance in State Middle Schools in West Prabumulih District. The population in this study were all teachers at Public Middle Schools in West Prabumulih District, namely Public Middle School 4 and Public Middle School 9 in Prabumulih City 116 people, totaling 90 people. The sampling technique in this research is random sampling technique. This research uses descriptive analysis methods using a quantitative approach. Data collection techniques use data by means of observation, questionnaires and documentation. Analysis using the t test and F test. The results of the research show that: (1) there is an influence of the principal's leadership on teacher performance in State Middle Schools in West Prabumulih District; (2) the principal's academic supervision influences teacher performance in State Middle Schools in West Prabumulih District; and (3) the principal's leadership and the principal's academic supervision simultaneously have an influence on teacher performance in State Middle Schools in West Prabumulih District of 79.2% and the remaining 20.8% is influenced by other variables not examined in this research. Keywords: Leadership; Academic Supervision; Teacher Performance